2011
DOI: 10.1186/gb-2011-12-12-r121
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the bloom syndrome helicase increases DNA ligase 4-independent genome rearrangements and tumorigenesis in aging Drosophila

Abstract: BackgroundThe BLM DNA helicase plays a vital role in maintaining genome stability. Mutations in BLM cause Bloom syndrome, a rare disorder associated with cancer predisposition and premature aging. Humans and mice with blm mutations have increased frequencies of spontaneous mutagenesis, but the molecular basis of this increase is not well understood. In addition, the effect of aging on spontaneous mutagenesis in blm mutants has not been characterized. To address this, we used a lacZ reporter system in wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
1
15
1
Order By: Relevance
“…Gene deletion events can also be produced in the context of chromosomal rearrangements leading to deletion, inversion, and duplication of the genomic region surrounding the Notch locus. Significantly, our findings differ markedly from previous reports of “tumors” in aged male and female fly midguts, consisting of a thickened tissue (Garcia et al., 2011), and from midgut dysplasia during aging caused by stimulation of ISC proliferation due to gut microbiota (Biteau et al., 2008, Buchon et al., 2009a). The neoplasias that we identified occur only in males, consist of ISC/EE cells, and have a clear somatic genetic origin.…”
Section: Discussioncontrasting
confidence: 99%
“…Gene deletion events can also be produced in the context of chromosomal rearrangements leading to deletion, inversion, and duplication of the genomic region surrounding the Notch locus. Significantly, our findings differ markedly from previous reports of “tumors” in aged male and female fly midguts, consisting of a thickened tissue (Garcia et al., 2011), and from midgut dysplasia during aging caused by stimulation of ISC proliferation due to gut microbiota (Biteau et al., 2008, Buchon et al., 2009a). The neoplasias that we identified occur only in males, consist of ISC/EE cells, and have a clear somatic genetic origin.…”
Section: Discussioncontrasting
confidence: 99%
“…5) can also be seen in Drosophila melanogaster Blm mutants (Garcia et al 2011), suggesting the existence of a common mechanism for DEL formation in a Blm-deficient background. BLM helicase acts to unwind secondary DNA structures at the telomere (Sfeir et al 2009).…”
Section: Possible Molecular Mechanisms For Genomic Rearrangements Indmentioning
confidence: 86%
“…Using the same lacZ reporter used in our study, changes in mutation load and lifespan have been recently observed in flies mutant for the bloom syndrome (BLM) DNA repair helicase [48]. Because dysregulation of Myc and BLM are both linked to cancer in humans [1], [49], we compared the molecular nature of mutations induced by these two genes in flies.…”
Section: Discussionmentioning
confidence: 96%